SERUM BIOMARKERS AND PREDICTIVE ALGORITHMS FOR EPITHELIAL OVARIAN CANCER DETECTION: A SYSTEMATIC REVIEW OF CA-125, HE4, AND ROMA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epithelial ovarian cancer is frequently diagnosed at an advanced stage because early symptoms are vague and reliable population-level screening strategies remain unavailable. Serum biomarkers such as cancer antigen 125 (CA-125) and human epididymis protein 4 (HE4), along with the Risk of Ovarian Malignancy Algorithm (ROMA), have been widely evaluated for differentiating malignant from benign adnexal masses and improving preoperative risk stratification.Objective: This systematic review aimed to evaluate the diagnostic utility of CA-125, HE4, and ROMA in epithelial ovarian cancer detection, with emphasis on sensitivity, specificity, menopausal status, early-stage disease, and clinical applicability.Methods: A systematic search was conducted using PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, Google Scholar, and reference screening. Studies were eligible if they evaluated CA-125, HE4, ROMA, or combined biomarker strategies in women with suspected ovarian malignancy, pelvic masses, or adnexal masses and reported diagnostic accuracy outcomes. Data were extracted regarding study design, study population, biomarker thresholds, menopausal stratification, reference standard, sensitivity, specificity, area under the curve, and major diagnostic conclusions. Methodological quality was assessed using diagnostic accuracy principles and QUADAS-2 domains.Results: The search identified 892 records. After removal of 214 duplicates, 678 records were screened. A total of 587 records were excluded after title and abstract screening. Ninety-one full-text articles were assessed for eligibility, of which 67 were excluded. Finally, 24 studies were included in the systematic review. CA-125 demonstrated acceptable sensitivity, particularly in advanced-stage epithelial ovarian cancer, but had limited specificity in benign gynecological disease and premenopausal women. HE4 generally showed higher specificity than CA-125 and was less frequently elevated in benign conditions such as endometriosis. ROMA improved overall risk classification by integrating CA-125, HE4, and menopausal status. However, diagnostic performance varied across studies due to differences in disease stage, histological subtype, assay platform, cutoff value, renal function, and study population.Conclusion: CA-125 remains useful in ovarian cancer assessment but is limited as a stand-alone diagnostic marker. HE4 improves specificity, while ROMA offers better combined risk stratification in women with adnexal masses. These biomarkers should be interpreted alongside clinical findings, menopausal status, imaging features, and histopathological confirmation. None of the evaluated strategies is sufficient as an independent screening tool for average-risk asymptomatic women.